2017
DOI: 10.1016/j.watres.2016.11.001
|View full text |Cite|
|
Sign up to set email alerts
|

Pesticides drive risk of micropollutants in wastewater-impacted streams during low flow conditions

Abstract: Micropollutants enter surface waters through various pathways, of which wastewater treatment plants (WWTPs) are a major source. The large diversity of micropollutants and their many modes of toxic action pose a challenge for assessing environmental risks. In this study, we investigated the potential impact of WWTPs on receiving ecosystems by describing concentration patterns of micropollutants, predicting acute risks for aquatic organisms and validating these results with macroinvertebrate biomonitoring data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 48 publications
9
175
1
3
Order By: Relevance
“…Previous studies looking into the effects of simultaneous exposure to high temperature and pollutants have reported higher frequency and impact of synergistic effects of these stressors (summarised by, e.g., Holmstrup et al., ). The concentrations of pollutants in these studies were, however, higher than what is normally observed in natural environments (Munz et al., ). The magnitude of synergism may thus depend on both the chemical concentration and the exposure temperature (e.g.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous studies looking into the effects of simultaneous exposure to high temperature and pollutants have reported higher frequency and impact of synergistic effects of these stressors (summarised by, e.g., Holmstrup et al., ). The concentrations of pollutants in these studies were, however, higher than what is normally observed in natural environments (Munz et al., ). The magnitude of synergism may thus depend on both the chemical concentration and the exposure temperature (e.g.…”
Section: Discussioncontrasting
confidence: 67%
“…While no data on the MP concentrations in pond water in the area exist, MPs are common in freshwater systems in the central Europe (e.g. Munz et al, 2016;Wittmer et al, 2010).…”
Section: Model Organismmentioning
confidence: 99%
“…The outputs of the present study suggest strong simplifying patterns of risk in highly diverse sets of mixture exposures. Land use–related chemical signatures appear to exist, whereby mixture effects are commonly caused by a few chemicals (for a given toxicological endpoint), although those few chemicals differ with land use and time (Munz et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…This consisted of low concentrations of pharmaceuticals, a hormone, a herbicide, a fungicide, a pesticide, an insecticide, a corrosion inhibitor and a sweetener (Supplementary material Appendix 1 Table A1) similar to the mix described in Stamm et al (2016) and Salo et al (2017). These chemicals and concentrations were chosen because they are commonly observed in freshwater ecosystems in central Europe (Wittmer et al 2010, Munz et al 2017) and known to cause organismal level effects in snails (Salo et al 2017). To ensure constant exposure to MPs and sufficient water quality, water was changed every second day in all experimental units.…”
Section: Experimental Designmentioning
confidence: 99%